AI Literacy in Information Technology Education: Challenges, Competency Frameworks, and Curriculum Implications - Ayu Widya Listari; Andi Nurqamal Ady Putra; Andi Gagah Purnama; Herianti Herianti; Andi Hasri Tri Ulandari (Universitas Cahaya Prima, 2026)
The rapid development of Artificial Intelligence (AI) requires educational systems to integrate new competencies that extend beyond basic technical skills. In the context of Information Technology Education (ITE), AI literacy emerges as a strategic competency encompassing conceptual understanding, applied skills, and ethical awareness in the use of AI-based technologies. Although various AI literacy frameworks have been developed globally, studies that systematically integrate competency dimensions, implementation challenges, and curricular implications within the ITE context remain limited, particularly in Indonesia. This study aims to synthesize the literature on the conceptual construction of AI literacy, identify challenges in its educational implementation, and outline implications for the development of an adaptive ITE curriculum. The research employs a Systematic Literature Review of national and international articles published between 2018 and 2026, sourced from indexed academic databases using structured selection criteria. The findings indicate that AI literacy is multidimensional, encompassing conceptual, applicative, and ethical dimensions that must be integrated with the strengthening of computational thinking and critical digital literacy. The primary challenges in implementation include limited teacher competencies, the rapid evolution of AI technologies, and infrastructural disparities. The novelty of this study lies in integrating global competency frameworks with the implementation context of ITE in Indonesia into a unified conceptual model. These findings provide a strategic foundation for the development of a competency-based ITE curriculum that is responsive to AI-driven digital transformation.